Multimodal Recognition of Emotions in Music and Facial Expressions - Proverbio, Alice Mado; Camporeale, Elisa; Brusa, Alessandra (Frontiers in Human Neuroscience, 2020)
The aim of the study was to investigate the neural processing of congruent vs. incongruent affective audiovisual information (facial expressions and music) by means of ERPs (Event Related Potentials) recordings. Stimuli were 200 infant faces displaying Happiness, Relaxation, Sadness, Distress and 32 piano musical pieces conveying the same emotional states (as specifically assessed). Music and faces were presented simultaneously, and paired so that in half cases they were emotionally congruent or incongruent. Twenty subjects were told to pay attention and respond to infrequent targets (adult neutral faces) while their EEG was recorded from 128 channels. The face-related N170 (160-180 ms) component was the earliest response affected by the emotional content of faces (particularly by distress), while visual P300 (250-450 ms) and auditory N400 (350-550 ms) responses were specifically modulated by the emotional content of both facial expressions and musical pieces. Face/music emotional incongruence elicited a wide N400 negativity indicating the detection of a mismatch in the expressed emotion. A swLORETA inverse solution applied to N400 (difference wave Incong. – Cong.), showed the crucial role of Inferior and Superior Temporal Gyri in the multimodal representation of emotional information extracted from faces and music. Furthermore, the prefrontal cortex (superior and medial, BA 10) was also strongly active, possibly supporting working memory. The data hints at a common system for representing emotional information derived by social cognition and music processing, including uncus and cuneus.